2021
DOI: 10.1155/2021/9933389
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effect of Khat in Rat Embryos and Fetuses

Abstract: Khat (Catha edulis Forsk) is a plant consumed by many people in Eastern Africa, including Ethiopia, and Southern Arabia to be stimulated. There are several human and animal studies on khat that provide information about its toxic effects. However, the potential toxic effects of khat on embryos and fetuses have not been elucidated. The aim of the present study was to investigate the embryotoxic and fetotoxic effects of khat exposure during the earliest period of gestation in rats. Pregnant Wistar albino rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…This might indicate a higher safety level of the plant extract to influence the aforementioned fetal outcome indices. However, further experiments shall be conducted to rule out possible compensational changes during late gestational periods [ 13 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This might indicate a higher safety level of the plant extract to influence the aforementioned fetal outcome indices. However, further experiments shall be conducted to rule out possible compensational changes during late gestational periods [ 13 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gross external morphology, visceral morphology, and skeletal evaluations are the key fetal developmental endpoints that were investigated to determine the effect of E. schimperi [ 16 , 19 ]. The present study revealed that there were no significant dose-related differences in gross and visceral fetal morphological indices among E. schimperi treatment groups and the control groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations